Isolation and Screening of Antibiotics Producing Actinomycetes from Soil of Khumbu Region above 5000m Altitude - Rai, Bishan; Limbu, Dhiren Subba; Bantawa, Kamana; Adhikari, Dibhya; Thakuri , Khusbu Shahi (Himalayan Journal of Science and Technology, 2024)
Actinomycetes are gram positive bacteria having fungi-like structure, which recently gained a considerable interest because of their importance in not just treatments but also organic matter recycling. This study aimed to isolate and evaluate Actinomycetes from soil samples for their potential to produce antibiotics collected from different places of Khumbu region above altitude of 5000 m in Nepal. The isolates were meticulously retrieved from soil samples using the enriching medium of Starch Casein Agar. Primary Screening and secondary screening were conducted employing the perpendicular streak method and the agar well assay technique, each applied in a systematic and precise manner. This research compared the antibacterial efficacy of purified extracts with various test bacteria. The actinomycetes with broad spectrum antibacterial activity was selected for fermentation and was converted into the crude extract. Then crude extracts were partially purified by solvent extraction method. In the preliminary screening, the perpendicular streak technique was employed, only 2 (3%) of the isolates exhibited antibacterial activity against majority of test bacterium among 3 Gram positive bacteria and 5 Gram negative bacteria. S27 displayed the largest zone of inhibition to Klebsiella pneumoniae and S34 showed highest zone of inhibition against MRSA. Both isolates showed broad spectrum in the secondary screening with higher level of statistical significance, both S34 and S27 having p value of .00 and Chi-square value of 119.169a and 91.157a respectively.